Genetic Modification of Bergera koenigii for Expression of the Bacterial Pesticidal Protein Cry1Ba1 - Ravanfar, Seyed Ali; Achor, Diann S.; Killiny, Nabil; Shilts, Turksen; Chen, Yuting; El-Mohtar, Choaa; Stelinski, Lukasz L.; Bonning, Bryony C.; Orbović﻿﻿﻿, Vladimir (Frontiers in Plant Science, 2022)
The curry leaf tree, Bergera koenigii, is highly attractive to the Asian citrus psyllid, Diaphorina citri, which vectors the bacterial causative agent of citrus greening or huanglongbing disease. This disease has decimated citrus production in Florida and in other citrus-producing countries. As D. citri exhibits high affinity for feeding on young leaves of B. koenigii, transgenic B. koenigii expressing bacteria-derived pesticidal proteins such as Cry1Ba1 have potential for D. citri management when planted in or adjacent to citrus groves. Importantly, the plant pathogenic bacterium that causes citrus greening does not replicate in B. koenigii. Transgenic plants of B. koenigii were produced by insertion of the gene encoding the active core of the pesticidal protein Cry1Ba1 derived from Bacillus thuringiensis. The transformation success rate was low relative to that of other citrus, at 0.89%. T-DNA integration into the genome, and cry1ba1 transcription in transgenic plants was confirmed. Transgenic plants expressing Cry1Ba1 differed from wild type plants, with differences in photosynthesis parameters and hormone levels in some instances, and a marked delay in wilting of detached leaves. The gut epithelium of D. citri fed on transgenic plants was severely damaged, consistent with Cry1Ba1-mediated pore formation, confirming expression of the pesticidal protein by transgenic B. koenigii. These results demonstrate that transgenic B. koenigii expressing bacteria-derived pesticidal proteins can be produced for potential use as trap plants for suppression of D. citri populations toward protection of citrus groves from citrus greening.